Fourier algebras of parabolic subgroups - Knudby, Søren (MATHEMATICA SCANDINAVICA, 2017)
We study the following question: given a locally compact group when does its Fourier algebra coincide with the subalgebra of the Fourier-Stieltjes algebra consisting of functions vanishing at infinity? We provide sufficient conditions for this to be the case. As an application, we show that when P is the minimal parabolic subgroup in one of the classical simple Lie groups of real rank one or the exceptional such group, then the Fourier algebra of P coincides with the subalgebra of the Fourier-Stieltjes algebra of P consisting of functions vanishing at infinity. In particular, the regular representation of P decomposes as a direct sum of irreducible representations although P is not compact.